Comparative bioavailability of two oral formulations of clopidogrel: Determination of clopidogrel and its carboxylic acid metabolite (SR26334) under fasting and fed conditions in healthy subjects - Brvar Nina; Lachance Sylvain; Lévesque Ann; Breznik Marjanca; Cvitkovič Marčič Lea; Merslavič Mateja; Grabnar Iztok; Mateovič-Rojnik Tatjana (Acta Pharmaceutica)
Two randomized, single dose, 2-period, 2-sequence crossover studies were conducted to evaluate the comparative bioavailability of two clopidogrel formulations under fasting and fed conditions. Assessment of bioequivalence was based upon measurement of plasma concentrations of the parent drug, clopidogrel, and its major (inactive) metabolite, clopidogrel carboxylic acid, using improved methanol-free extraction. Bioequivalence of Krka’s formulation to the innovator’s formulation was demonstrated under both fasting and fed conditions on 205 volunteers. Confidence intervals for AUC0-t, AUC0-inf and Cmax of clopidogrel and its main metabolite were well within the acceptance range of 80.00 to 125.00 %. Food substantially increased the bioavailability of clopidogrel from both formulations, while no effect of food on the extent and rate of exposure to the metabolite was observed. The effect of food was comparable between the two formulations, as indicated by the same direction and rank of food impact on the bioavailability of both formulations.